The effect of music during warm-up on consecutive anaerobic performance in elite adolescent volleyball players - Eliakim, M.; Meckel, Y.; Nemet, D.; Eliakim, A. (International Journal of Sports Medicine, 2007)
Music is believed to improve athletic performance. The aim of the present study was to determine the effect of arousing music during warm-up on anaerobic performance in elite national level adolescent volleyball players. Twenty-four players (12 males and 12 females) performed the Wingate Anaerobic Test following a 10-minute warm-up with and without music (two separate occasions, random order). During warm-up with music, mean heart rate was significantly higher. Following the warm-up with music, peak anaerobic power was significantly higher in all volleyball players (10.7 ± 0.3 vs. 11.1 ± 0.3 Watts/kg, p < 0.05, without and with music, respectively). Gender did not influence the effect of music on peak anaerobic power. Music had no significant effect on mean anaerobic output or fatigue index in both genders. Music affects warm-up and may have a transient beneficial effect on anaerobic performance.